Analisis Rasio Pendapatan Petani Sayuran Sawi Dengan Petani Padi Di Kecamatan Sukorambi Kabupaten Jember - Suherman Suherman (STIE Mandala Jember, 2019)
Agirbisnis in the field of food crops, especially Mustard vegetables and rice have favorable prospects. The mustard vegetable farming in the Sokorambi sub-district on a micro scale, is a hereditary effort with traditional methods, the title of this research is: Analysis of the ratio of mustard vegetable growers to rice farmers in Sukorambi District, Jember Regency. The specific objectives of this study are: To find out the reasons why farmers prefer to grow mustard or rice vegetables, to analyze the comparison of farmers' income between planting mustard vegetables and planting rice.The method used for achieving goals is: Profit Analysis, Analysis of farm efficiency with the R / C Ratio approach, Comparison of income of mustard vegetable farmers with rice farmers.The results showed that the R / C ratio for the two commodities is greater than one, which shows that it is worth trying. The advantage of mustard vegetable farmers is significantly different compared to the benefits of rice farmers.